A new Australian online and phone mental health support service for young people living with cancer. (April 2014) - Patterson, Pandora; McDonald, Fiona EJ; Orchard, Peter
Objective: The purpose of CanTeen's E-Mental Health Service for Young People Living With Cancer (YPLWC) is to meet the unique psychosocial needs of young people (12–24 years) in Australia impacted by cancer (either as a patient or family member of someone with cancer). Conclusions: This online platform will provide the primary site where all YPLWC can find information, connect with others going through a similar experience, express their feelings, utilise tools for support and access professional psychosocial support services that will meet their individual needs. The overall outcome of the service will be to ensure that the YPLWC visiting the site experience optimal psychological wellbeing. Ultimately, the service's value will be in improving the lives of young people who engage with it and the follow-on effect that this will have on their families and communities in the long-term.